PEMETAAN HOTS SISWA BERDASARKAN STANDAR PISA DAN TIMSS UNTUK MENINGKATKAN MUTU PENDIDIKAN - Tini Hartini; Muhamad Ali Misri; Indah Nursuprianah (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2018)
The purpose of this research was to mapped the higher order thinking skills of students in solving PISA and TIMSS standards based test item based on indicators that had been compiled, as one of the effort to determine the right thing to do to increase the quality of education. The indicators in this research were the ability of analysis, evaluation, and creation. This research use a descriptive qualitative and quantitative approach. The data collection methods in this research were documentation, test, and interview. From 71 students spread across many Junior High Islamic Scoolls in Cirebon city, 2 students classified as having high order thinking skills with moderate level. Students in moderate level are found to be able to perform analysis, evaluation, and creation well in resolving some of the problems. Furthermore, 69 students are not able to perform analytical skills, evaluation, and creation well in solving all the problems, so they are considered to have low level in high order thinking skill. The difference of the studentâ€™s ability due to the lack of motivation students and teachers in improving the ability of HOTS in learning. An increase in HOTS of students can be done to improve standards evaluation, improve the quality of the process and the result of learning, as well as increase the motivation students and teachers. This research can be applied to measure studentâ€™s high order thinking skill in order to increase Â the quality of education according to international standards.